The Effect of Innovative Learning Models on Students’ Critical Thinking Skills at Eleventh Grade Students of Pustek Vocational High School - Suhaepi, Muhammad Iip (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2026)
Critical thinking skills are essential competencies for vocational high school students because they help learners analyze information, evaluate problems, make logical decisions, and apply knowledge in real-life situations. However, students’ critical thinking skills are often limited when classroom activities are dominated by conventional teacher-centered instruction. Therefore, innovative learning models are needed to create more active, meaningful, and student-centered learning experiences. his study aimed to investigate the effect of innovative learning models on students’ critical thinking skills at eleventh grade students of Pustek Vocational High School. The research used a quantitative approach with an experimental design. The learning process was conducted by applying innovative learning models that encouraged students to participate actively through problem solving, discussion, collaboration, inquiry, and project-based activities. Data were collected through a critical thinking skills test and analyzed to determine the improvement of students’ critical thinking performance after the implementation of the learning models. The results indicated that the implementation of innovative learning models had a positive effect on students’ critical thinking skills. Students showed improvement in identifying problems, analyzing information, giving logical arguments, drawing conclusions, and evaluating solutions. The learning activities also increased students’ confidence, participation, and ability to express ideas during classroom discussions.